2016
DOI: 10.1021/acs.jpcb.6b06775
|View full text |Cite
|
Sign up to set email alerts
|

Lowered pH Leads to Fusion Peptide Release and a Highly Dynamic Intermediate of Influenza Hemagglutinin

Abstract: Hemagglutinin (HA), the membrane-bound fusion protein of the Influenza virus, enables the entry of virus into host cells via a structural rearrangement. There is strong evidence that the primary trigger for this rearrangement is the low pH environment of a late endosome. To understand the structural basis and the dynamic consequences of the pH trigger, explicit-solvent molecular dynamics simulations were employed to investigate the initial stages of the HA transition. Our results indicate that lowered pH desta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Time-resolved pH-jump experiments on membrane-bound proteins show great promise for capturing these conformational changes in HA (53). A slower transition of the B loop and a long-lived intermediate may provide functional benefits by providing additional free-energy drive for membrane fusion and contributing extra time to the association among multiple HAs (54). We can speculate that this intermediate state is followed by the final rearrangement of S4 and S5, providing sufficient free energy to stabilize the final structure and possibly bringing the viral and cell membranes together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-resolved pH-jump experiments on membrane-bound proteins show great promise for capturing these conformational changes in HA (53). A slower transition of the B loop and a long-lived intermediate may provide functional benefits by providing additional free-energy drive for membrane fusion and contributing extra time to the association among multiple HAs (54). We can speculate that this intermediate state is followed by the final rearrangement of S4 and S5, providing sufficient free energy to stabilize the final structure and possibly bringing the viral and cell membranes together.…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration for the HA 2 rearrangement is its pH sensitivity. Several regions of HA are suggested to respond to lowered pH, including dissociation of HA 1 (59), destabilization of the fusion peptide burial pocket (54,60), and stability of the B-loop trimeric coiled coil (5). Interestingly, isolated HA 2 folds into the postfusion structure at both neutral and low pH (61), suggesting a limited role for pH in HA 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that at increasingly acidic condition, prior to activation, HA becomes primed for fusion peptide release, adding further support to this emerging mechanistic model. These recent studies suggest that in the early stages of fusion activation HA adopts a dynamic fusion-peptide-released intermediate state [22,27,33,80,81,[84][85][86][87].…”
Section: Despite Their Common Architectures Activation Mechanisms Anmentioning
confidence: 95%
“…The "uncaging" model for HA activation suggests that HA1 acts as a cage or clamp containing the spring-loaded HA2 fusion machine; whereupon low pH releases the HA1 cage, allowing rapid and irreversible activation of the spring-loaded HA2 fusion machine (7,(11)(12)(13). By contrast, a "fusion peptide release" model suggests that low pH first stimulates the release of the HA2 N-terminal fusion peptide hook from its sequestered pocket in the core of HA2 before HA1 head domains dissociating from each other (12,(14)(15)(16)(17)(18)(19)(20)(21). In this model, the exposed fusion peptide, tethered to a highly dynamic HA2 subunit, is deployed and available to engage with the target membrane before the large-scale refolding of HA2 into the postfusion, hairpin conformation (22).…”
Section: Introductionmentioning
confidence: 99%